Tradisi Sodoran Tengger sebagai Alat Diplomasi Budaya Indonesia melalui Pembelajaran BIPA - Siti Nur Azizah; Sony Sukmawan; Ismatul Khasanah (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
Culture in BIPA learning as a tool of cultural diplomacy has become an interesting theme for researchers. The cultural aspect of BIPA is also related to the cultural closeness of BIPA students to the place where they study (the area/city where BIPA is studied in Indonesia). This study aimed to identify and describe the use of the Sodoran Tengger tradition in BIPA learning of B2 level activities to increase Indonesian knowledge competence. This research is a qualitative type with a descriptive method. The use of descriptive analysis methods is carried out to describe the facts, which are then studied with the relevant theory. The results of this study are the use of the Tengger Sodoran dance as BIPA teaching material and the use of traditional sodoran fairy tales as BIPA teaching materials. Utilizing Sodoran Tengger's local tradition material on aspects of the meaning of dance moves and fairy tales is an innovative and interesting choice for BIPA class teachers. The existing aspects can be explored and collaborated into various fun learning activities. Besides improving linguistic competence, it is also a means of introducing local Tengger culture (Javanese culture) to BIPA students.